Mrs Sidhu investigates. Series 1 [videorecording (DVD)] - Pannu, Suk (Mrs. Sidhu investigates (Television programs), 2023)
Mrs Sidhu is a caterer with a taste for solving mysteries. Her sleuthing turns into an unofficial partnership with dour DCI Burton, who reluctantly accepts that together they make the perfect pairing to fight crime.